Prospects of Clean Cooking Energy in Africa - Transition Pathways and Implications - Kihedu, Joseph H.; Msuya, Juma N. (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Despite abundant renewable energy resources, African countries still suffer from energy poverty, particularly in cooking. Up to 2022, about 74% of the African population had no access to clean cooking energy. With focus to Sub-Saharan African population, 90% has no access to clean cooking energy which decrease by 7% when kerosene is included. Traditional cooking, which involves the use of charcoal and firewood, is associated with health problems, environmental degradation,socioeconomic issues, and gender inequality. Transitioning to clean cooking energy not only promises significant health benefits but also offers opportunities for sustainable economic development and environmental preservation. In this study, the desk research method was used, which involved compiling raw published data such as research articles, government reports, implemented project reports, and published statistics. The following are the findings of this study: Firstly, for the improvement of health, environment, and social economic issues, the community must transition from traditional cooking to clean cooking. Secondly, despite the promises posed by energy transition, upfront cost and technological challenges remain to be a challenge that need action. Thirdly, the government should weigh up on clean cooking technologies investment, program sustainability, and engaging the community. Lastly, the government should structure the clean cooking agenda based on the resource’s proportionality in the region. Generally, to improve the welfare of the community, energy <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">transition from traditional to clean cooking stands as the main piece, however, the government should intentionally intervene for the <span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">transition to be realized.